Retrospective study on the effectiveness of medroxyprogesterone acetate in the treatment of ER-positive/HER2-negative post-menopausal advanced breast cancer: an additional analysis of the JBCRG-C06 Safari study. (8th December 2022) - Kawaguchi, Hidetoshi; Yamamoto, Yutaka; Saji, Shigehira; Masuda, Norikazu; Nakayama, Takahiro; Aogi, Kenjiro; Anan, Keisei; Ohtani, Shoichiro; Sato, Nobuaki; Takano, Toshimi; Tokunaga, Eriko; Nakamura, Seigo; et al.
Abstract: Background: Only old evidence exists to back up the use of medroxyprogesterone acetate. Therefore, this study aimed to explore the factors that influence the time to treatment failure of medroxyprogesterone acetate in real-world settings as late-line treatment. Methods: This was a cohort study that used the database of the Safari study on oestrogen receptor-positive post-menopausal advanced breast cancer (UMIN000015168). We created Kaplan–Meier curves for time to treatment failure with medroxyprogesterone acetate. Further, univariate and multivariate analyses were performed using a Cox hazard model of the clinicopathological factors involved in the time to treatment failure of medroxyprogesterone acetate. Results: From the 1031 patients in the Safari study, 279 patients were selected as the population for the analysis of effectiveness of medroxyprogesterone acetate monotherapy. In the analysis of medroxyprogesterone acetate by treatment line, the median time to treatment failure was 3.0 months for third-line treatment and 4.1 months for fourth and subsequent treatment lines. In cases where medroxyprogesterone acetate was used as a third-line or later endocrine treatment, multivariate analysis showed that the length of the disease-free interval was correlated with the length of time to treatment failure of medroxyprogesterone acetate ( P  = 0.004). With medroxyprogesterone acetate monotherapy as the fourth-line or later treatment, 20% of the patients achieved a time to treatment failure of 12 months or longer. Conclusion: In actual clinical practice, patients treated with medroxyprogesterone acetate alone as the fourth or subsequent treatment lines showed a time to treatment failure of 4 months, suggesting that there is merit in using medroxyprogesterone acetate even in late treatment lines, especially in patients with long disease-free interval and those who are difficult to treat using other antineoplastic agents. Abstract : Medroxyprogesterone acetate can be helpful in sequential endocrine therapy for patients, even in late treatment lines, especially in patients with a long disease-free interval and those who are difficult to treat using other antineoplastic agents.